THE RELATIONSHIP BETWEEN PERSONAL HYGIENE AND SKIN DISEASES IN SCAVENGERS AT THE BANTAR GEBANG INTEGRATED WASTE TREATMENT PLACE (TPST), CIKETING UDIK VILLAGE, BANTAR GEBANG SUB-DISTRICT, BEKASI CITY IN 2023 - Auliya Rahmah; Nur Romdhona; Ernyasih; Fini Fajrini (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Due to their involvement with trash and unclean surroundings, scavengers are more likely to get skin conditions. According to the Ciketing Udik Health Center profile, skin illness was the most prevalent ailment in 2021, accounting for 382 occurrences. The purpose of this study was to ascertain how the prevalence of skin diseases among scavengers at the Bantar Gebang Integrated Waste Treatment Site (TPST), Ciketing Udik Village, Bantar Gebang District, in 2023 related to skin hygiene, hand, foot, and nail hygiene, clothing cleanliness, and hair hygiene. This study design is cross-sectional and employs a descriptive-analytic research methodology. An incidental sampling strategy was used to get a sample of 60 individuals, and a chi square test was used for analysis. An incidental sampling strategy was used to get a sample of 60 individuals, and a chi square test was used for analysis. The findings indicate that the incidence of skin illness among scavengers at Bantar TPST Gebang Ciketing Udik Village is correlated with skin cleanliness (pv=0.000), hand, foot, and nail hygiene (pv=0.000), garment cleanliness (pv=0.000), and hair hygiene (pv=0.002). The prevalence of skin diseaseses is correlated with the cleanliness of the skin, hands, feet, and nails as well as the cleanliness of clothing and hair. Dermatitis, urticaria, and tinea versicolor are the most prevalent skin conditions. Personal hygiene (skin, hands, feet, nails, clothing, and hair) is recommended for scavengers. It is recommended that the puskesmas conduct thorough and recurring counseling in the interim.